Microbiologists M.R. Sharipova and A.M. Mardanova are Talented Students and Teachers - Trushin, Maxim (Bangladesh Journal of Infectious Diseases, 2023)
The history of the formation and development of the microbiological discipline at the Imperial Kazan University began in the middle of the XIX century. Then the first attempts were made to control infectious processes in the Kazan province (cholera, influenza, smallpox). With the advent of the microscope, university researchers have gained a new opportunity to observe microorganisms. At the end of the 19th century, the issues of medical and general microbiology were widely discussed in the scientific community of the city. At the very beginning of the twentieth century, the Bacteriological Institute was opened at the Faculty of Medicine, which became the flagship of these studies. However, microbiological research began to develop at other faculties of Kazan University already under Soviet rule (the work of A.P. Ponomarev and his student S.I. Limanova-Kolosova). They mainly dealt with issues of ecological and geological microbiology. At the very beginning of the Great Patriotic War, the University Laboratory of Microbiology was headed by M.I. Belyaeva, who in 1969 achieved the opening of the Department of Microbiology as part of the Biology and Soil Faculty of Kazan State University named after V.I. Ulyanov-Lenin. She was the founder of a new modern direction — the study of enzymes of microorganisms. Her students, who later became professors, R.P. Naumova and I.B. Leshchinskaya, have already educated their talented followers. This article is devoted to a review of the scientific and pedagogical activities of professors M.R. Sharipova and A.M. Mardanova, employees of the Department of Microbiology of Kazan Federal University. Bangladesh Journal of Infectious Diseases, December 2023;10(2):104-109